Association of substance use disorders and drug overdose with adverse COVID-19 outcomes in New York City: January–October 2020. (26th December 2020) - Allen, Bennett; El Shahawy, Omar; Rogers, Erin S; Hochman, Sarah; Khan, Maria R; Krawczyk, Noa
ABSTRACT: Background: Evidence suggests that individuals with history of substance use disorder (SUD) are at increased risk of COVID-19, but little is known about relationships between SUDs, overdose and COVID-19 severity and mortality. This study investigated risks of severe COVID-19 among patients with SUDs. Methods: We conducted a retrospective review of data from a hospital system in New York City. Patient records from 1 January to 26 October 2020 were included. We assessed positive COVID-19 tests, hospitalizations, intensive care unit (ICU) admissions and death. Descriptive statistics and bivariable analyses compared the prevalence of COVID-19 by baseline characteristics. Logistic regression estimated unadjusted and sex-, age-, race- and comorbidity-adjusted odds ratios (AORs) for associations between SUD history, overdose history and outcomes. Results: Of patients tested for COVID-19 ( n  = 188 653), 2.7% ( n  = 5107) had any history of SUD. Associations with hospitalization [AORs (95% confidence interval)] ranged from 1.78 (0.85–3.74) for cocaine use disorder (COUD) to 6.68 (4.33–10.33) for alcohol use disorder. Associations with ICU admission ranged from 0.57 (0.17–1.93) for COUD to 5.00 (3.02–8.30) for overdose. Associations with death ranged from 0.64 (0.14–2.84) for COUD to 3.03 (1.70–5.43) for overdose. Discussion: Patients with histories of SUD and drug overdose may be at elevated risk of adverse COVID-19 outcomes.